(untitled) (Revista Internacional de Folkcomunicação, 2025)
This article is based on a bibliographic and documentary research with the objective of understanding the meaning of research in Folkcommunication, pointing to the need to incorporate the term “praxis” to reinforce the ideal of resistance. An approximation is made, especially based on the concept of Paulo Freire and its interface with Luiz Beltrão’s theory. In addition to the conceptual proposition, and based on studies in Communication and Gender, two objects - examples of folkcommunication praxis - are chosen for case study: the Youtube channel Tempero Drag by Rita von Hunty (Guilherme Terreri Lima Pereira) and the Instagram page @posithividades by the psychoanalyst Lucian Ambrós. A common factor is that they are also popularizers of scientific knowledge. As a concluding element, we point to the counter-hegemonic epistemic bias as a characteristic of Folkcommunication studies.